Arabidopsis ANAC092 regulates auxin‐mediated root development by binding to the ARF8 and PIN4 promoters. Issue 9 (18th February 2019) - Xi, Dandan; Chen, Xu; Wang, Yuxia; Zhong, Ruiling; He, Jianmei; Shen, Jiabin; Ming, Feng
Abstract: Auxin is an important plant hormone that is essential for growth and development due to its effects on organogenesis, morphogenesis, tropisms, and apical dominance. The functional diversity of auxin highlights the importance of its biosynthesis, transport, and associated responses. In this study, we show that a NAC transcription factor, ANAC092 (also named AtNAC2 and ORESARA1), known to positively regulate leaf senescence and contribute to abiotic stress responses, also affects primary root development. Plants overexpressing ANAC092 had altered root meristem lengths and shorter primary roots compared with the wild‐type control. Additionally, expression of the proANAC092::GUS was strongly induced by indole‐3‐acetic acid. Quantitative real‐time RT‐PCR (qRT‐PCR) analysis revealed that the YUCCA2, PIN, and ARF expression levels were downregulated in ANAC092 ‐overexpressing plants. Moreover, yeast one‐hybrid and chromatin immunoprecipitation assays confirmed that ANAC092 binds to the promoters of AUXIN RESPONSE FACTOR 8 ( ARF8 ) and PIN‐FORMED 4 ( PIN4 ). Furthermore, a dual‐luciferase assay indicated that ANAC092 decreases ARF8 and PIN4 promoter activities. We also applied a CRISPR/Cas9 system to mutate ANAC092 . The roots of three of the analyzed mutants were longer than normal. Collectively, our findings indicate that ANAC092 negatively affects root development by controlling the auxin pathway. Abstract : Root development plays essential roles in plant growth. Our study showed that a NAC family transcription factor, ANAC092, can bind to ARF8 and PIN4 promoters, thus negatively regulating auxin‐mediated primary root length.